Combination of Dental Capping Agents With LowLevel Laser Therapy Increases the Cell Viability Percent of Stem Cells From Apical Papilla (SCAPs) - Zafari, Jaber; Karkehabadi, Hamed; Nikzad, Forough; Esmailnasab, Sogand; Abbasi Javan, Zahra; Javani Jouni, Fatemeh (Journal of Lasers in Medical Sciences, 2022)
Introduction: Stem cells from apical papillae (SCAPs) are adult stem cells capable of differentiating into multiple cell lineages. Dental pulp capping materials promote the differentiation of stem cells of the apical papilla (SCAPs). Higher proliferation and cell viability of stem cells have been reported upon exposure to low-level laser therapy (LLLT). However, there is limited evidence on the combinational effects of dental pulp capping materials and low-level laser radiation. In this study, the effects of dental dressing materials combined with laser on the SCAPs viability will assess. Methods: SCAPs isolation was performed from two immature third molar teeth through collagenase type I enzymatic activity. Isolated stem cells were then cultured with DMEM and α-MEM media enriched with 15% and 10% FBS, respectively. After reaching 70-80% confluency, cells were seeded in a 96-well plate. Cell viability percent was assessed using MTT assay after treatment by MTA, EMD, CEM, and LLLT alone and in combination for 24, 48, and 168 h. Results: A combination of MTA, CEM, EMD, and LLLT could result in significantly increased SCAPs viability as compared with other treatment groups. Increased levels of SCAPs proliferation and viability were observed in groups treated with the combination of MTA and CEM with EMD. SCAPs viability percent in all defined times was reduced with MTA and CEM treatment. Conclusion: LLLT is a stimulator of SCAPs cell viability percent and differentiation rate when applied with dental capping agents such as MTA, EMD, and CEM, which is a therapeutic option for stem cell-based therapy.